2000
DOI: 10.1046/j.1463-1318.2000.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost effectiveness of self‐expanding metal stents in the management of malignant left‐sided large bowel obstruction

Abstract: Stenting of acute large bowel obstruction is a cost-effective procedure with a reduction in total hospital stay and expenditure compared with surgical decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 12 publications
2
34
0
5
Order By: Relevance
“…Though the cost associated with colonic stenting is higher than the cost of performing a diverting colostomy for the initial management of acute, malignant colonic obstruction, the incremental cost associated with providing one additional improved patient outcome is very reasonable. Previously published cost-effectiveness analyses (17,25) have revealed results similar to our findings in the present study. In one analysis (25) performed using United Kingdom health care costs, preoperative colonic stenting resulted in a mean net savings of £685 per stented patient compared with performance of the Hartmann's procedure, mainly due to a shorter length of hospital stay for stented patients.…”
Section: Discussionsupporting
confidence: 92%
“…Though the cost associated with colonic stenting is higher than the cost of performing a diverting colostomy for the initial management of acute, malignant colonic obstruction, the incremental cost associated with providing one additional improved patient outcome is very reasonable. Previously published cost-effectiveness analyses (17,25) have revealed results similar to our findings in the present study. In one analysis (25) performed using United Kingdom health care costs, preoperative colonic stenting resulted in a mean net savings of £685 per stented patient compared with performance of the Hartmann's procedure, mainly due to a shorter length of hospital stay for stented patients.…”
Section: Discussionsupporting
confidence: 92%
“…6,11 In addition, this procedure may shorten the length of hospital stay and be more cost-effective than surgeries. 6,[16][17][18] In contrast to colorectal cancers, in which the obstructions develop from intraluminal growth, obstructions by metastatic or invasive noncolorectal cancer develop from extrinsic compression. Because obstruction and tumor characteristics differ between colorectal cancer and extrinsic tumor-related obstruction, the results of SEMS insertion are expected to be different.…”
Section: Discussionmentioning
confidence: 99%
“…A small retrospective study from the UK in 1998 showed that the mean net saving from palliative stenting compared to surgical decompression was £1769, whereas the saving from stenting as a bridge to surgery followed by elective resection, compared to emergency Hartmann's operation followed by elective reversal was £685. 42 A RCT from Greece comparing stenting and colostomy for palliation of patients with inoperable malignant partial colonic obstruction showed very small difference in the costs, with the stent group being 6.9% (132 euros) more expensive per patient. 32 Another study from Switzerland reported stenting to be 19.7% less costly than surgery.…”
Section: Colonic Stentsmentioning
confidence: 99%